Almost $η$-conformal Ricci solitons in $(LCS)_{3}$-manifolds - Siddiqi, Mohd Danish; Chaubey, Sudhakar K. (Sarajevo Journal of Mathematics, 2022)
The aim of the present paper is to study the properties of three dimensional Lorentzian concircular structure manifolds ($(LCS)_{3}$-manifolds) endowed with almost $η$-conformal Ricci solitons. Also, we discuss the $η$-conformal gradient shrinking Ricci solitons on $(LCS)_{3}$-manifolds. Finally, the examples of almost $η$-conformal Ricci soliton on an $(LCS)_{3}$-manifold are provided in the region where $(LCS)_{3}$-manifold is expanding.